Śrī Devanārāyaṇa kathā: Māravāḏa kā pāramparika gāyana - Bhopā, Hukmārāma; Gūjara, Moṭārāma; Malik, Aditya (South Asian studies, 2003)
Folk song on Devanārāyana, Hindu deity recited and performed in Rajasthan; transcription of the recordings